Analysis of SAGE data in human platelets: Features of the transcriptome in an anucleate cell - Dittrich, Marcus; Birschmann, Ingvild; Pfrang, Julia; Herterich, Sabine; Smolenski, Albert; Walter, Ulrich; Dandekar, Thomas (Thrombosis and Haemostasis, 2006)
A comprehensive SAGE (serial analysis of gene expression) library of purified human platelets was established. Twenty-five thousand (25,000) tags were sequenced, and after removal of mitochondrial tags, 12,609 (51%) non-mitochondrial-derived tags remained, corresponding to 2,300 different transcripts with expression levels of up to 30,000 tags per million. This new, highly purified SAGE library of platelets is enriched in specific transcripts.The complexity in terms of tag distribution is similar to cells that are still able to replenish their mRNA pool by transcription.We show that our SAGE data are consistent with recently published microarray data but show further details of the platelet transcriptome, including (i) longer UTR regions and more stable folding in the enriched mRNAs, (ii) biologically interesting new candidate mRNAs that show regulatory elements, including elements for RNA stabilization or for translational control, and (iii) significant enrichment of specific, highly transcribed mRNAs compared to a battery of SAGE libraries from other tissues. Among several regulatory mRNA elements known to be involved in mRNA localization and translational control, CPE elements are in particular enriched in the platelet transcriptome. mRNAs previously reported to be translationally regulated were found to be present in the library and were validated by real-time PCR. Furthermore, specific molecular functions such as signal transduction activity were found to be significantly enriched in the platelet transcriptome.These findings emphasize the richness and diversity of the platelet transcriptome.
Keywords: Platelet; transcriptome; SAGE; signaling pathway; post-transcriptional regulation; RNA element; gene ontology